ChemInform Abstract: Metal‐Free Radical Perfluoroalkylation of (Hetero)arenes. Issue 25 (5th June 2015) - Zhong, Sabilla; Hafner, Andreas; Hussal, Christoph; Nieger, Martin; Braese, Stefan
Abstract: Inexpensive and commercially available perfluorocarboxylic anhydrides are used as source of perfluoroalkyl radicals for the perfluoroalkylation of various arenes, such as benzene derivatives, furans, thiophenes, and pyrroles.